Nexrutine® preserves muscle mass similar to exercise in prostate cancer mouse model. Issue 16 (27th August 2019) - Patel, Darpan I.; Wallace, Derek; Abuchowski, Kira; Rivas, Paul; Gallegos, Amber; Musi, Nicolas; Kumar, Addanki Pratap.
Abstract: Muscle loss is a debilitating side effect to prostate cancer (PCa) experienced by nearly 60% of men. The purpose of this study was to test the hypothesis that Nexrutine ®, a bark extract from the Phellodendrum amurense, can protect against prostate cancer induced muscle loss in a similar manner as exercise, using the transgenic adenocarcinoma of mouse prostate (TRAMP) model. Forty‐five, 8‐ to 10‐week old TRAMP mice were randomized to either control, Nexrutine ® (600 mg/kg pelleted in chow) or exercise (voluntary wheel running). Mice were serially sacrificed at weeks 4, 8, 12, and 20, at which time either the left or right gastrocnemius muscle was harvested, weighted, and frozen. Proteolysis inducing factor (PIF), ubiquitin, and NF‐κB concentrations were quantified using ELISA kits. Nexrutine ® and exercise were equally able to protect TRAMP mice against PCa‐induced muscle loss ( P  = 0.04). Both interventions decreased intramuscular PIF concentrations at 20 weeks compared to control ( P  < 0.05). A treatment effect was also observed when all time points were combined with exercise significantly lowering PIF concentrations ( P  < 0.01). Exercise significantly lowered intramuscular ubiquitin concentrations in weeks 4, 8, and 20 compared to control mice ( P  < 0.001). A treatment effect was also observed with exercise significantly lowering ubiquitin compared to control mice ( P  < 0.001). No significant changes were observed for NF‐κB. The results of this investigation demonstrate that PCa‐induced muscle loss can be attenuated with the herbal supplement Nexrutine ® . This investigation provides preliminary evidence to support continued research into Nexrutine ® as a potential exercise analog in protecting against muscle loss. Abstract : The results of this investigation demonstrate that prostate cancer‐related muscle loss can be attenuated with the herbal supplement Nexrutine®. This investigation provides preliminary evidence to support continued research into Nexrutine® as a potential exercise analog in protecting against muscle loss.